Evaluation of grip strength in children: The ergonomic design used in the development of secure lids for packaging - Paschoarelli, Luis Carlos [UNESP]; Dahrouj, Laura Schaer [UNESP] (My University, 2012)
Packaging design should provide safety, comfort, efficiency and aesthetic satisfaction, as well as consider user capacity, especially usability and accessibility when opening. Product access should be easy for users with limited capabilities (i.e., the elderly) and difficult for those restricted from using it (i.e., children). The purpose of this study was to verify manual grip (torque) strength while opening a container of bleach. A total of 102 subjects (51 females) between 2 to 5 years old participated in the study. A static torque screwdriver was placed inside three mockup bleach containers. In all mock-ups, there was a significant increase (p = 0.05) in grip strength ability according to age. The three analyzed lids were of different dimensions and the results indicated that this variable had a strong influence on the application of torque. The recommended dimensions for the lids of products with toxic potential must be near those of the lid with the smallest diameter, whose design reduces children’s capacity to apply torque. These results may contribute to better usability and security for packaging design.
Keywords: Ergonomic design; Grip strength; Lids; Packaging design